The centennial of the Yellow Fever Commission and the use of informed consent in medical research - Güereña-Burgueño Fernando (Instituto Nacional de Salud Pública, 2002)
The year 2000 marked the centennial of the discovery of the mode of transmission of yellow fever. Informed consent was systematically used for the first time in research. This process was the result of a complex social phenomenon involving the American Public Health Association, the US and Spanish Governments, American and Cuban scientists, the media, and civilian and military volunteers. The public health and medical communities face the AIDS pandemic at the beginning of the 21st Century, as they faced the yellow fever epidemic at the beginning of the 20th Century. Current medical research dilemmas have fueled the debate about the ethical conduct of research in human subjects. The AIDS pandemic is imposing enormous new ethical challenges on the conduct of medical research, especially in the developing world. Reflecting on the yellow fever experiments of 1900, lessons can be learned and applied to the current ethical challenges faced by the international public health research community.